2015
DOI: 10.1016/j.virol.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic doses of irradiation activate viral transcription and induce apoptosis in HIV-1 infected cells

Abstract: The highly active antiretroviral therapy reduces HIV-1 RNA in plasma to undetectable levels. However, the virus continues to persist in the long-lived resting CD4+ T cells, macrophages and astrocytes which form a viral reservoir in infected individuals. Reactivation of viral transcription is critical since the host immune response in combination with antiretroviral therapy may eradicate the virus. Using the chronically HIV-1 infected T lymphoblastoid and monocytic cell lines, primary quiescent CD4+ T cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 115 publications
0
45
0
Order By: Relevance
“…Several humanized mouse models have been developed to study HIV-1 replication and latency (30,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Mice containing human CD4 T cells support both R5-and X4-tropic HIV-1 infections (reviewed in reference 45) and respond to treatment with ART, typically administered by intraperitoneal (i.p.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several humanized mouse models have been developed to study HIV-1 replication and latency (30,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Mice containing human CD4 T cells support both R5-and X4-tropic HIV-1 infections (reviewed in reference 45) and respond to treatment with ART, typically administered by intraperitoneal (i.p.)…”
mentioning
confidence: 99%
“…injections (34-36, 38-42, 44) or, less commonly, by addition to drinking water (40,43) or food (37,41,44). The presence of a latent reservoir in ART-treated humanized mice is inferred by observing virus rebound following withdrawal of ART (37,38,41,(43)(44)(45), with estimates of the size of the reservoir obtained by measuring the total HIV-1 DNA load in the human cells in the animals by qPCR (30,37,39,41,43). The QVOA has also been adapted for mouse models, although the requirement for large numbers of cells in order to detect latent, reactivatable, and infectious genomes in ART-treated mice required pooling of several tissues (30,34,35,38,43).…”
mentioning
confidence: 99%
“…Using the SCID-hu model, it has been shown that IL-7 induces substantial expression of latent HIV while having minimal effects on the cell phenotype [68]. In a recent study using HIV-1 infected NSG humanized mice with undetected basal levels of viral replication, a dramatic increase in HIV-1 RNA in plasma, lung and brain tissues were observed following ionizing radiation-induced cellular stress [69]. …”
Section: Introductionmentioning
confidence: 99%
“…28 Recent clinical studies that included analysis of CD4 + T-cell count in the blood from cancer patients infected or not with HIV-1 indicated that radiation therapy reduced the CD4 + cell count more dramatically in HIV-1-infected individuals. 25,29 Treatment with NNRTIbased ART exacerbated this effect.…”
mentioning
confidence: 99%
“…31,32 Nevertheless, the combination of moderate doses of IR with chemical compound, PKC agonist bryostatin 1, enhanced transcription activation and cell killing in monocyte/macrophages. 28 This suggests that the IR effect is cell-type specific and that infected T cells are more prone to apoptosis with IR, whereas IR with LRAs is needed to kill infected myeloid cells.…”
mentioning
confidence: 99%